A new genus and species of Perforissidae (Hemiptera: Fulgoromorpha) from mid-Cretaceous Kachin amber. (October 2020) - Luo, Cihang; Jiang, Tian; Szwedo, Jacek; Wang, Bo; Xiao, Chuantao
Abstract: A new genus and species of planthopper, Lanlakawa changdaensis gen. et sp. nov., is described based on a well-preserved specimen from mid-Cretaceous Kachin (Burmese) amber. This is the ninth genus of the extinct family Perforissidae and the sixth genus of the subfamily Cixitettiginae. The new genus mainly differs from the five previously described genera in tegmen venation and the number of teeth in tibial pectens. Previous researches of sensory pits and wing-coupling apparatus are briefly reviewed.